Hormone-related risk factors for breast cancer in women under age 50 years by estrogen and progesterone receptor status: results from a case–control and a case–case comparison - Ma, Huiyan; Bernstein, Leslie; Ross, Ronald K; Ursin, Giske (Breast cancer research : BCR, 2006)
It has been suggested that hormonal risk factors act predominantly on estrogen receptor and progesterone receptor (ER/PR)-positive breast cancers. However, the data have been inconsistent, especially in younger women. We evaluated the impact of age at menarche, pregnancy history, duration of breastfeeding, body mass index, combined oral contraceptive use, and alcohol consumption on breast cancer risk by ER/PR status in 1,725 population-based case patients and 440 control subjects aged 20 to 49 years identified within neighborhoods of case patients. We used multivariable unconditional logistic regression methods to conduct case-control comparisons overall as well as by ER/PR status of the cases, and to compare ER+PR+ with ER-PR- case patients. The number of full-term pregnancies was inversely associated with the risk of ER+PR+ breast cancer (ptrend = 0.005), whereas recent average alcohol consumption was associated with an increased risk of ER+PR+ breast cancer (ptrend = 0.03). Neither of these two factors was associated with the risk of ER- PR- breast cancer. Late age at menarche and a longer duration of breastfeeding were both associated with decreased breast cancer risk, irrespective of receptor status (all ptrend< or = 0.03). Our results suggest that the number of full-term pregnancies and recent alcohol consumption affect breast cancer risk in younger women predominantly through estrogen and progesterone mediated by their respective receptors. Late age at menarche and breastfeeding may act through different hormonal mechanisms.